1990
DOI: 10.1016/s0022-5347(17)39748-3
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral Microwave Hyperthermia for Benign Prostatic Hyperplasia: Preliminary Clinical and Pathological Results

Abstract: Transurethral microwave hyperthermia is a new conservative treatment modality for benign prostatic hyperplasia. We treated 15 patients with 915 MHz. microwaves delivered transurethrally by a helical applicator. Of the patients 12 showed substantial objective and subjective improvement of obstructive outflow parameters. Significant improvement in objective study parameters included increased mean flow rate (p less than 0.00021), decreased mean residual volume (p less than 0.00001) and decreased mean prostatic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

1991
1991
1994
1994

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(29 citation statements)
references
References 13 publications
2
27
0
Order By: Relevance
“…Baert et al [16], in a study of 15 patients who under went transurethral microwave therapy, demonstrated a successful outcome in 12 (80%) patients. The 3 patients who failed to improve after treatment had either a large residual urine volume or significant middle lobe hyperTablel.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Baert et al [16], in a study of 15 patients who under went transurethral microwave therapy, demonstrated a successful outcome in 12 (80%) patients. The 3 patients who failed to improve after treatment had either a large residual urine volume or significant middle lobe hyperTablel.…”
Section: Discussionmentioning
confidence: 98%
“…The minimally invasive ther apies available include prostatic stenting [12], balloon dilatation [13], laser treatment (TULIP, ELAP) [14] and transrectal or transurethral microwave therapy [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clear objective and subjective improvement was observed. A conclusion was made that transurethral hy perthermia is a safe and well-tolerated treatment [9], Patients who are at poor risk for surgery could benefit from this therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple sessions are used. The dura tion of each treatment is 1 h, and 5-10 sessions separated by 72-96 h are recommended [17,18], Subjective im provement was observed in about 70% of the patients with a mean increase in peak flow (3-4 ml) [17,18] (ta ble 2). One may question the role played by repeated cath eterization in the interpretation of these results.…”
Section: Transurethral Thermotherapymentioning
confidence: 99%